ARM Instructions and Part II - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
The data transfer instructions are used to transfer data from memory to registers and from registers to memory and they are Load (LDR) and Store (STR) instructions.
Citation Key Alias: lens.org/013-090-628-194-319
Keywords: dept.csc